IMPLEMENTATION OF A UNMANNED GROUND VEHICLE (UGV) NRSM FOR DISASTER RESCUE OPERATIONS IN FLOODS, EARTHQUAKES, AND LANDSLIDES - Nur Rachman Supadmana Muda; Bilqis Faranadila (Jurnal Cakrawala Ilmiah, 2026)
The NRSM (National Rescue Support Machine) Unmanned Ground Vehicle (UGV) is developed to enhance disaster rescue operations in flood, earthquake, and landslide environments where human access is limited and hazardous. The proposed system integrates a high-mobility tracked platform, multi-sensor victim detection modules, real-time communication systems, and semi-autonomous navigation control to support search, monitoring, and evacuation missions. The UGV is designed to traverse unstable terrain, debris-filled areas, and partially flooded zones while maintaining stable communication with rescue operators. Experimental evaluations indicate that the NRSM UGV significantly improves rescue performance by increasing operational speed, victim detection accuracy, and evacuation efficiency compared to conventional manual rescue methods. The integration of thermal imaging, LiDAR sensing, and onboard payload transport capabilities enables rapid identification and safe evacuation of victims while minimizing risks to rescue personnel. These results demonstrate that the NRSM UGV provides an effective technological solution for modern disaster-response operations, with strong potential for further enhancement through fully autonomous navigation and multi-robot cooperative deployment.